Enhancing English Language Writing Skills: An Evaluation of the Efficacy of Grammarly Application - Rizky Eka Prasetya; Didik Hariyadi Raharjo (English Department - University of Sultan Ageng Tirtayasa, 2023)
This study investigated the effectiveness of using the Grammarly application in teaching English language writing skills. A mixed-methods approach was utilised to collect data from 100 English language learners with diverse backgrounds and levels of proficiency. Participants were randomly assigned to either an experimental group that used Grammarly or a control group that received traditional writing instruction. The study collected quantitative and qualitative data, including pre-and post-test assessments of writing skills and surveys and interviews exploring participants' perceptions of Grammarly. Quantitative data analysis showed a significant improvement in the experimental group's writing skills regarding grammatical accuracy, vocabulary use, and overall writing quality. The effect size was also calculated to determine the magnitude of the difference between the two groups. Qualitative data analysis revealed that participants positively perceived Grammarly, including its user-friendliness and ability to provide personalized feedback. The findings suggest that Grammarly effectively teaches English language writing skills and can supplement traditional writing instruction. The study provides insights into the benefits and limitations of Grammarly and its potential impact on English language learners' writing skills. This research contributes to the ongoing discussion on integrating technology in language learning and provides implications for language instructors and developers of writing applications.